KARAKTERISTIK MADU HUTAN LEBAH Apis Dorsata DAERAH SULAWESI TENGGARA DITINJAU DARI SIFAT FISIKA-KIMIA - Desy Nurhasanah Sari (Universitas Cokroaminoto Palopo, 2023)
Forest honey is a natural liquid produced by Apis dorsata bees that has many health benefits. The quality of honey in Indonesia is based on quality standards determined by the Indonesian National Standard (SNI) 8664:2018. The quality of honey can be determined based on its physico-chemical properties. This study aims to determine the physical and chemical characteristics of forest honey from Lambusa Village, Konda Subdistrict, Konawe Regency, Southeast Sulawesi. Some parameters tested were water content, ash content, viscosity, pH, reducing sugar (glucose), Hydroxy Methyl Furfuraldehyde (HMF) and metal contamination of As, Pb and Cd in honey. The results showed that forest honey has a water content of 21.07% w/w, ash content of 0.25% w/w, viscosity of 10.26 poise, acidity of 42.16 mL N NaOH/kg, reducing sugar of 73.24% w/w and HMF content of 18.13 mg/kg, and is not contaminated with arsenic (As), cadmium (Cd) and lead (Pb) metals. From the results of this test, it can be concluded that forest honey from Lambusa village, Konda district, Konawe district, Southeast Sulawesi has physico-chemical properties that meet SNI 8664:2018.